Psychoeducational intervention for sexual risk behavior and promiscuity in a college student population - Muhammad Hisyam Syafii; Azam Syukur Rahmatullah (Nur Science Institute, 2025)
This bibliometric study explored psychoeducational interventions targeting sexual risk behaviors among college students from 1990 to 2024. A total of 1,847 publications were analyzed from Web of Science, Scopus, PubMed, PsycINFO, and ERIC. Temporal mapping revealed three developmental stages: emergence (1990–2005), rapid expansion (2006–2015), and consolidation (2016–2024), with an average annual growth rate of 8.4%. Most studies originated from North America, particularly the United States (68.3%). The Information-Motivation-Behavioral Skills Model was the most frequently applied framework (16.9%), followed by the Theory of Planned Behavior (15.6%). Group-based psychoeducational workshops demonstrated the greatest impact (Cohen’s d = 0.67) and strong cost-effectiveness, while digital interventions expanded outreach but struggled with sustained engagement. The interventions were most effective in reducing sexual coercion (40.7%) and improving STI status discussions (40.8%). Over time, research evolved from disease prevention to holistic wellness promotion. Nevertheless, regional disparities and limited cultural adaptation remain key challenges for global implementation.